Antibacterial Activity of Turmeric (Curcuma domestica Val.) Extract on the Growth of Klebsiella sp.: In Vitro - Hardiati, Aprilia; Satriani, Muchamad Armand (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2025)
Klebsiella sp. is one of the causes of bacterial diseases that attack large farm animals and poultry. Treatment of infections caused by these bacteria is using antibiotics. Cases of antibiotic resistance against Klebsiella sp. encouraging researchers to study spice plants as antibacterial, especially turmeric (Curcuma domestica Val.). Research related to the antibacterial activity of turmeric against Klebsiella spp. not much has been done. Therefore, this study aimed to determine the antibacterial activity of turmeric extract against Klebsiella sp. in vitro. re-identified by testing on MacConkey agar, triple sugar iron agar, and IMViC (indole, methyl red, Voges-Proskauer, citrate). Overall results showed the characteristics of Klebsiella sp. Making turmeric powder simplicia extract by maceration method followed by evaporation using a spray dryer. Turmeric extract was diluted with dimethyl sulfoxide (DMSO). The antibacterial activity test of turmeric extract (20%, 40%, 60%, 80%, 100%) was carried out on Mueller-Hinton agar that had been given wells. Chloramphenicol (30 g) was used as a positive control and DMSO as a negative control. The test was carried out with three repetitions. The mean inhibition zone diameter of three repetitions was 20.00 mm; 0.00mm; 10.17mm; 10.67 mm; 10.67 mm; 11.17 mm and 12.17 mm for positive control, negative control, 20-100% turmeric extract. Based on the results of phytochemical tests, turmeric extract contains flavonoids, alkaloids, quinones and triterpenoids. Turmeric extract with concentrations of 20%, 40%, 60%, 80% and 100% had the activity to inhibit the growth of Klebsiella sp. with a strong category on in vitro testing.